The New Left: Legacy and Continuity - Lexier, Roberta (Labour / Le Travail, 2008)
The article reviews the book, "The New Left: Legacy and Continuity," edited by Dimitrios Roussopoulos.
Keywords: BOOKS -- Reviews; NEW Left: Legacy & Continuity, The (Book); New Left; Nonfiction; ROUSSOPOULOS, Dimitrios